TINDAK TUTUR ILOKUSI DALAM IKLAN RADIO RRI PRO 2 PONTIANAK 101.8 FM - Wulandari, Wulandari; Patriantoro, Patriantoro; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
This study aims to analyze the types and functions of illocutionary speech acts contained in radio advertisements for RRI Pro 2 Pontianak 101.8 FM. The method used in this research is a descriptive method with a qualitative research form. The source of the data in this study was the RRI Pro 2 Pontianak radio advertisement. The data collection technique used was the technique of recording, listening freely, engaging competently, and taking notes. The data collection tool uses a recording device in the form of gadgets and stationery. The technique for testing the validity of the data in this research is diligent observation and adequacy of references. The results of data analysis on the types of illocutionary speech acts in RRI Pro 2 Pontianak radio advertisements consist of 4 types of illocutionary acts, namely assertive 25 data, directive 11 data, expressive 2 data, commissive 2 data, and no declarative. The illocutionary function consists of 12 functions, namely the function of stating 9 data, the function of reporting 12 data, the function of complaining 1 data, the function of expressing opinions 3 data, the function of advising 2 data, the function of ordering/ordering 4 data, the function of inviting 3 data requests, the function of request 1 data, function requests 1 data, function criticizes 2 data, function promises 1 data, and function offers 1 data. The implementation of learning in this study was in the form of E-modules of odd semester advertisement texts with KD 3.3 and 4.3